Synthesis of Polyaniline Composites with Grinded Leaves of Polyalthia longifolia, Syzygium cumini, Alstonia scholaris and Madhuca longifolia and Study of Their Structural, Electrical and Dielectric Properties - Kanwal, Farah; Batool, Aisha; Rasool, Sadia; Naseem, Shahzad; Rehman, Rabia (Asian Journal of Chemistry, 2014)
Polyaniline composites has successfully been synthesized with well grinded leaves of Polyalthia longifolia, Syzygium cumini, Madhuca longifolia and Alstonia scholaris in an acidic medium by chemical oxidation method at room temperature. Fourier transform infrared (FT-IR) spectroscopy confirmed the formation of composites. All prepared samples were characterized for their electrical and dielectric properties. Polyaniline/Polyalthia longifolia composite offer enhanced dielectric properties with dielectric constant four times greater than pure polyaniline, suitable for its application as passivation layer for thin film transistor.